Comparative characteristics of stress-resistant and non-stress-resistant individual profiles - Boltivets, Sergii (2021)
The article presents typical profiles of stress-resistant and non-stress-resistant individuals by certain components. Summarizing the factor analysis substantive elements, we identified four leading components of the internal structure of indicators of personality stress relationships by the informative weight of variables: personal; social; typological, and behavioral. We found out that stress-resistant individuals are characterized by a high level of balance, confidence and activity, emotional and volitional self-control, low levels of stress, personal and situational anxiety, high levels of motivation, general and professional internality, readiness for activity, high level of functional system. Stress-resistant individuals are characterized by a high level of assertiveness, activity, prosociality, the search for social contacts and social support. At the same time, the typical profile of non-stressful individuals is characterized by inverse patterns - a significantly lower level of direct and indirect indicators of stress resistance, among the behavioral strategies for overcoming stress typical in the profile were manipulative actions, avoidance actions, aggressive actions.